Short term and long term aging effects of modified rubber polymer asphalt binder - Putra Jaya, Ramadhansyah; E., Shaffie; J., Ahmad; A. K., Arshad (2018)
This paper presents a laboratory study on the effect of short term and long term aging of modified rubber polymer binder (MRB). Nowadays, the conventional asphalt binder from refining process of crude oil was used in pavement construction. However, due to aging process, asphalt binder becomes stiff and brittle which will eventually lead premature failures in pavement. The rheological effect of aging modified asphalt binder was evaluated through Rotational Viscometer (RV) and Dynamic Shear Rheometer (DSR) tests. The conventional asphalt binder was blended with 0%, 2%, 4% and 6% rubber polymer by weight of asphalt binder. The samples were tested and evaluated for rutting resistance, G*/sin (δ) and fatigue resistance, G*sin (δ) characteristics. Results showed that the there is an increase in viscosity for MRB asphalt binder. Meanwhile, based on the rheological performance analysis with DSR, MRB has significantly increase the rutting (G*/sin) and fatigue G*sin (δ) resistance. As a conclusion, results showed that the MRB can enhance the asphalt pavement performance.